Розумний органайзер ліків з функцією нагадування - Савченко, Є. Ю. (ХНУРЕ, 2024)
The multifactorial problem of reducing patient adherence to treatment was considered in the work. It has been established that one of the negative factors associated with the patient himself is non-compliance with medication. This can lead to serious health problems and lack of positive effect from treatment. The problem solution is to create a “smart” organizer with a reminder function. The organizer is controlled by the Arduino UNO board. The device is configured using buttons; a reminder is a message on the display, as well as a sound and a light signal. A delay function of taking medications has also been implemented.
Keywords: розумний органайзер ліків; функція нагадування